ANALISIS CEMARAN LOGAM BERAT TIMBAL (Pb) PADA MAKANAN DAN MINUMAN : STUDI LITERATUR - Audi Ichsani Aribowo; Bunga Nur Annisa; Nena Vauziah Sary; Lina Nurfadhila; Marsah Rahmawati Utami (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2022)
Heavy metals are defined as the transition elements that have a high atomic mass, are toxic, and cannot be broken down by living organisms. Metal Lead (Pb) is one of the heavy metals which are widely distributed in the environment. Heavy metal lead is one of the causes of serious health problems because it can cause disturbances to the human body. Therefore, the aim of this literature review is to present an illustration and up-to-date data on the analytical methods used for food and beverages contaminated with lead heavy metal (Pb). The methodology of this research is a literature review study from several databases such as Science Direct, Pubmed, and Google Scholar with a limitation of publication in the last 10 years. The results of a literature review from the analysis of Pb metal contamination in food and beverages, there are several techniques that can be utilized to analyze and various factors that cause the amount of lead (Pb) levels such as the atomic absorption spectrophotometer (AAS) method.